If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(4x+8)-2(4-6x)=0
We add all the numbers together, and all the variables
5(4x+8)-2(-6x+4)=0
We multiply parentheses
20x+12x+40-8=0
We add all the numbers together, and all the variables
32x+32=0
We move all terms containing x to the left, all other terms to the right
32x=-32
x=-32/32
x=-1
| (1.2x+3.8)/4=(5.2x+1.8)/6 | | 40y-7=12y^2 | | -14=8-5x | | 5(3n-1)=55 | | 3(9+4x)=123 | | 2y-8=22-4y | | 2(7x-10)=36 | | 3x+2(x+7)=-11 | | 13×6=3x | | 38=4x+7x+5 | | (x-7/2)^2=0 | | -14-4x-3=3x-8-5x | | -x-3+7x=57 | | 6x+7=x+87 | | q(-4)+(1-q)(-4+5)=0 | | 1+8a=129 | | 1+8a=59 | | 3^4x+1=5 | | 8=10r+8-2r | | F=-6+2.5x | | X²-6x+20=0 | | 3(2x-4)=5x-(-3x+7) | | (x+9)2=121 | | 7y-2y-15=-5 | | X²+14x−176=0 | | X²+14x-176=0 | | 25x-5x=45+15 | | -x-59=85 | | 2a=-3a+1 | | x-39=74 | | -x+24=41 | | -9y=-2y-14 |